Factors Associated with the Outcome of Out-of-Hospital Cardiac Arrest at Emergency Department Phra Nakhon Si Ayutthaya Hospital - ลิ่มสุริยกานต์ วสันต์ (Journal of Preventive Medicine Association of Thailand, 2018)
Cardiac arrest is the most crisis emergency situation. Therefore, the developments and improvements of the resuscitation processes require the précised and completed data. The relevant factors that can improve the effectiveness of CPR process should be clarified. This study aimed to describe a relevant factor to outcome of Out-of-Hospital Cardiac Arrest patients with Cardiopulmonary Resuscitation at Emergency Department Phra Nakhon Si Ayutthaya Hospital. Method: The observational study, in Out-of-Hospital Cardiac Arrest patients with Cardiopulmonary Resuscitation at Emergency Department Phra Nakhon Si Ayutthaya Hospital between 2016 October, 1 and 2017 September, 30 Result: total 115 persons patient in this study were Male 75.65% and their mean age were 57.62 years. The most common cause of Cardiac Arrest was cardiovascular (54.78%). Most patients were transferred by EMS (49.57%). The witnessed arrests were 78.26%. the estimated time to first chest compression, mostly within 11-30 mins (64.35%). Bystander CPR rate were 2.61%. The initial EKG mostly was non-shock-able rhythm (92.17%). The estimated time to first dose adrenaline mostly was 0-10 min (75.65%). Total CPR time mostly within 11-30 min (46.96%). 45 persons had ROSC (62.61%). There was no factors associated with success in Cardiopulmonary Resuscitation in Out-of-Hospital Cardiac Arrest patients. Therefore, patients who had by stander CPR and who had shockable rhythm that received AED shock had higher rate of ROSC. Therefore, the results of the study should promote bystander CPR and AED at scene to success in Cardiopulmonary Resuscitation in Out-of-Hospital Cardiac Arrest patients.